Increased Relevance And Influence Of Free Prior Informed Consent, Redd, And Green Economy Principles On Sustainable Commons Management In Peru - Dall’Orso, Carlos A. M. Soria (Journal of Sustainable Development Law and Policy, 2025)
This paper examines unique opportunities provided by international discourses and practices of the Green Economy approach and valuation of ecosystem services (as promoted under the international climate change regime) on the sustainable management of indigenous forests and lands in Peru. It examines the influence of epistemological changes prompted by the United Nations Framework Convention on Climate Change (UNFCCC) on the improved understanding and conceptualization of the role of forests and sound natural resource management; and how these changes at the international level have positively impacted traditional land rights in Peru.1 It also analyses how increased development and financing of Reducing Emissions from Deforestation and Forest Degradation (REDD) processes and projects have enhanced the incorporation of interculturality into indigenous peoples’ public policy in Peru. The paper traces the influence of these international frameworks and processes in Peru during the Humala administration (2011-2016)- which is a significant turn-around from the position in which the Garcia administration (2006-2011) left the country after the loss of thirty-four (34) Peruvians on the morning of 5 June 2009. Since 2011, the Humala administration and indigenous peoples have fostered a common path to develop public policies that protects the needs of Amazonian peoples, particularly indigenous peoples. It has also promoted policies and legal frameworks that halt deforestation and promote sound environmental development in the form of a Green Economy with low carbon emissions and zero net deforestation in the context of the mandate of the Conference of the Parties (COP) 19, 20 and the 21 to follow up by the end of 2015.2 This paper discusses the Peruvian experience, most especially how international demands for greater transparency in forest management led to the evolution of the Prior Consultation Law and Forestry (FPIC) Law in Peru. It reviews the growing relevance and influence of the Peruvian FPIC law, its impact on sustainable forest management, and the opportunities and practical challenges it portends for sustainable commons management in Peru.